Seasonal Community Structure of Mesozooplankton in the Daya Bay, South China Sea - Liu, Huaxue; Li, Kaizhi; Huang, Honghui; Song, Xingyu; Yin, Jianqiang; Huang, Liangmin (Journal of Ocean University of China, 2013)
Mesozooplankton are key components of coastal ecosystems, linking the microbial food web to the classic food chain. In this study, species composition and abundance of mesozooplankton is studied for the Daya Bay in April （spring） and October （fall）, 2006. A total of 27 species of mesozooplankton were identified in spring and 58 species in fall. Dominant species were Oithona tenuis, Flaccisagitta enflata, Penilia avirostris and Centropages tenuiremis in spring, shifting to Microsetella norvegica, Oithona tenuis and Parvocalanus crassirostris in fall. Higher mesozooplankton abundance was found at Aotou Cove and Dapeng＇ao Cove compared to other stations, indicating the influence of eutrophication on mesozooplankton community in the Daya Bay. The outbreak ofNoctiluca scintillans bloom in spring reduced the species diversity and abundance of mesozooplankton.